The influence of tidal activities on hydrologic variables of Marang river, Terengganu, Malaysia - Mohd Ekhwan, Toriman; Muhammad Barzani, Gasim; Nur Hidayah, Ariffin (Malaysian Society of Analytical Sciences, 2015)
A study was conducted at Marang River, Terengganu on determination of hydrological variation of Marang River at seven sampling stations. Sampling stations were selected along Marang River started from downstream to upstream. Each station was located 2km apart from each other. Sampling was done twice; the first sampling was in 13 November 2012 (rainy season) and was repeated for second sampling on 24 February 2013 (dry season). Hydrological measurements of river such as velocity, river width and river depth were measured by using specific equipment. River velocity was measured by using flow meter (model FP101), river width was measured by using a rangefinder (model Bushnell 20-0001) and river depth was measured by using depth meter. Primary data of hydrological measurements of Marang River were measured and analyzed for each sampling station. Overall, station 1 shows the highest readings for most hydrological variables at both water tides during the first and second samplings. Station 1 that was located at the Marang River estuary identified by higher hydrological variables due to seawater movement during high tide as compared to stations 7 which located at the upstream. During dry season hydrological variables were slightly decrease since low freshwater flow from the upstream due to less rainfall intensity.